Bencana Galodo dalam Pandangan Masyarakat Dusun Tuo: Studi atas QS. Al-Hadid: 22 dan Ar-Rum: 41 - Fanisha, Olivia Ratu; Hafizzullah, Hafizzullah; Amril, Dapit (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2025)
The background of this study focuses on the impact of natural disasters that frequently strike Indonesia, particularly flash floods (galodo), which are triggered by natural factors and human actions that contribute to environmental degradation. The community of Jorong Dusun Tuo, as one of the affected areas, views the disaster as a fate from Allah as well as the result of human actions. This study aims to explore the understanding of the community in Jorong Dusun Tuo regarding the galodo natural disaster (landslide) and how this understanding is linked to the teachings of Islam found in Surah Al-Hadid verse 22 and Surah Ar-Rum verse 41. The main focus of this study is to: (1) analyze the interpretation of Surah Al-Hadid verse 22 and Surah Ar-Rum verse 41 in the context of disaster, (2) understand the reception of the Jorong Dusun Tuo community towards the causes and impacts of the galodo disaster, and (3) explore the relevance of Qur'anic teachings in the community's understanding of the disaster. This research is a field study with a qualitative approach and descriptive method. Data collection techniques include interviews, observations, and documentation. Primary data sources consist of victims of the galodo disaster, religious leaders, community figures, and members of the community involved in post-disaster recovery efforts. The results of the study show that the community of Jorong Dusun Tuo views the galodo disaster as a trial and a warning from God. (1) They understand that this disaster is part of the predestination decreed by Allah, as stated in Surah Al-Hadid verse 22. (2) They also associate the resulting damage with natural factors and human sins, such as environmental destruction, committing zina, abandoning worship, and distancing from God, which aligns with the message in Surah Ar-Rum verse 41. (3) This understanding carries significant meaning as a reflection on oneself, patience, and the enhancement of piety when facing life's trials, as well as a reminder to protect the environment.